Development of Forest Typology in Russia - Ivanova, N. S.; Zolotova, E. S. (International Journal of Bio-resource and Stress Management, 2023)
Forest typology holds the central position in modern forestry. We give an overview of research on forest typology in Russia. Forest typology in Russia actively developed and improved with respect to requests forestry throughout the entire period of its existence. It remains the necessary basis for preserving the biodiversity of land ecosystems and ensuring sustainable forest management amid the growing anthropogenic impact and climate change. The birth of scientific forest typology is associated with the name of G.F. Morozov. A biogeocoenotic approach to forest classification was offered by V.N. Sukachev. V.N. Sukachev developed classifications for boreal forests which had been little affected by economic activity. The biogeocoenotic approach proved effective there. However, when literally applied to commercial forests, the biogeocoenotic approach sometimes failed to deliver satisfying results. The exponential shrinkage of natural forests and the increasing share of dynamic secondary growth brought about the need to reflect the time-related forest changes in classifications. The origins of the genetic approach can be found in the writings of G.F. Morozov. The first satisfactory geo-genetic forest classification was built by B.A. Ivashkevich. B.P. Kolesnikov provided the theoretical grounding and main postulates for the approach. According to B.P. Kolesnikov, a geographical and genetic classification means a classification based on the forest origin and evolution patterns which takes account of all the forest ecosystem stages and can be used to predict their future changes. Currently forest typology develops as an interdisciplinary science. It integrates forestry, geobotanics, forest taxation, soil sciences, biogeography, geology, and landscape ecology. A new methodology is being developed. It is a synthesis of forest ecology and synergetic. It uncovers new reserves for the forest science development.